The Portrayal of Occultism in “The Call of Cthulhu” (1928) by H.P. Lovecraft - Evan Arnoldi Sebayang; Bayu Kristianto (k@ta: A Biannual Publication on the Study of Languange and Literature, 2021)
H.P. Lovecraft crafted an intricate mythos which initially did not find success until after his death, and his works, most notably “The Call of Cthulhu” (1928), were regarded to be a landmark towards the relevancy of occultism both in the field of literature and religious belief. The short story was regarded to be the staple of “cosmic horror” which Lovecraft applied to almost all of his stories. The paper analyze how “The Call of Cthulhu” influenced the belief of modern occultism, which can be inferred from the literary elements in the story. Further analysis will also identify how Lovecraft portrayed the subgenre “cosmic horror” to enhance the elements of occultism within the short story. In relation to the previous elements, the paper examine how a particular cult, Typhonian Order, was influenced by the elements of occultism used in the story.